Crystal structure of (RS)-(4-chlorophenyl)(pyridin-2-yl)methanol - Badiadka Narayana; Balladka K. Sarojini; Hemmige S. Yathirajan; Ravindranath Rathore; Christopher Glidewell (Acta Crystallographica Section E: Crystallographic Communications, 2016)
In the title racemic compound, C12H10ClNO, the dihedral angle between the benzene and pyridine rings is 74.34 (6)°. In the crystal, the molecules are linked by O—H...N hydrogen bonds, forming zigzag C(5) [001] chains in which alternating R- and S-configuration molecules are related by c-glide symmetry. In addition, inversion-related pairs of molecules are linked into dimers by pairs of weak C—Cl...π(pyridyl) interactions, which link the hydrogen-bonded chains into (100) sheets. Structural comparisons are drawn with a number of related compounds.